Updated distribution of Dilophus clavicornus Skartveit & Kaplan, 1996 (Diptera: Bibionidae), with new records from Romania, Montenegro and France - Jean-Paul Haenni; Alexandru-Mihai Pintilioaie; Daniel de Castro Schelesky-Prado; Jean-Jacques Porteneuve (Historia naturalis bulgarica)
Dilophus clavicornus Skartveit et Kaplan, 1996 (Diptera: Bibionidae: Bibioninae) is reported for the first time from Romania, Montenegro and France. Photos of male habitus, fore tibia and male terminalia are provided.